Experimental and modeling uncertainties in the validation of lower hybrid current drive. (27th July 2016) - Poli, F M; Bonoli, P T; Chilenski, M; Mumgaard, R; Shiraiwa, S; Wallace, G M; Andre, R; Delgado-Aparicio, L; Scott, S; Wilson, J R; Harvey, R W; Petrov, Yu V; et al.
Abstract: This work discusses sources of uncertainty in the validation of lower hybrid wave current drive simulations against experiments, by evolving self-consistently the magnetic equilibrium and the heating and current drive profiles, calculated with a combined toroidal ray tracing code and 3D Fokker–Planck solver. The simulations indicate a complex interplay of elements, where uncertainties in the input plasma parameters, in the models and in the transport solver combine and—in some cases—compensate each other. It is concluded that ray-tracing calculations should include a realistic representation of the density and temperature in the region between the confined plasma and the wall, which is especially important in regimes where the LH waves are weakly damped and undergo multiple reflections from the plasma boundary. Uncertainties introduced in the processing of diagnostic data as well as uncertainties introduced by model approximations are assessed. It is shown that, by comparing the evolution of the plasma parameters in self-consistent simulations with available data, inconsistencies can be identified and limitations in the models or in the experimental data assessed.